Fatty acid composition and antioxidant properties of seed oil from canarium spp - Noor Muhazah, Mazlan (Universiti Malaysia Sarawak (UNIMAS), 2015)
Seed from Canarium odontophyllum and C. megalanthum were analyzed for proximate composition, mineral content, fatty acid compositions and antioxidant properties. Results obtained showed the percentage moisture contents as 12.84% and 3.17%, ash as 4.05% and 2.65%, organic matter as 95.56% and 97.35% and fat content as 50.03% and 79.10% for C. odontophyllum and C. megalanthum, respectively. K, Mg, Ca and Na were analyzed as the macrominerals, Mn, Zn, Fe and Cu were identified as a microminerals and Pb and Cd as toxic minerals. The fatty acid compositions in both seed oil were analyzed using gas chromatography flame ionization detector and each component was identified based on fatty acid methyl ester (FAME) content. The fatty acid compositions in seed oil from C. odontophyllum and C. megalanthum was found to be 66.80% and 72.44% of saturated fatty acid, 32.04% and 27.58% monounsaturated fatty acid and 0.97% and 0.00% polyunsaturated fatty acid respectively. The antioxidant activity was assessed by 1, 1-diphenyl-2-picrylhydrazil (DPPH) scavenging activity assay and show that both seed oil from Canarium spp. has lower scavenging activity compared to L-ascorbic acid.